1987
DOI: 10.1148/radiology.164.2.3602389
|View full text |Cite
|
Sign up to set email alerts
|

Hypovolemic shock in children: abdominal CT manifestations.

Abstract: The authors describe a "hypoperfusion complex," seen on abdominal computed tomography, which consists of marked, diffuse dilatation of the intestine with fluid; abnormally intense contrast enhancement of the bowel wall, mesentery, kidneys, and/or pancreas; decreased caliber of the abdominal aorta and inferior vena cava; and moderate to large peritoneal fluid collections. This complex was present in three patients less than 2 years of age and was associated with severe injury and a poor outcome. Recognition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
3

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 0 publications
1
62
0
3
Order By: Relevance
“…Although there have been unfavorable reports on the reliability of CT to detect GI perforation [8,9], our findings lend weight to the body of literature advocating the role of CT [5][6][7][10][11][12]. Our 10-year review of hospital records identified no surgically confirmed GI perforation with a normal CT study, and all the CT studies in our perforation patients were abnormal.…”
Section: Discussionsupporting
confidence: 54%
“…Although there have been unfavorable reports on the reliability of CT to detect GI perforation [8,9], our findings lend weight to the body of literature advocating the role of CT [5][6][7][10][11][12]. Our 10-year review of hospital records identified no surgically confirmed GI perforation with a normal CT study, and all the CT studies in our perforation patients were abnormal.…”
Section: Discussionsupporting
confidence: 54%
“…However, it must also be remembered that hypovolemic shock syndrome (due to blood loss or neurologic injury) may result in transudation of intraperitoneal and retroperitoneal fluid [10,11] [8]. Fluid related to menstruation would be expected to predominate in the pouch of Douglas rather than in the upper part of the abdomen.…”
mentioning
confidence: 99%
“…In a study conducted on post-traumatic cases by Ryan et al (3), CT hypoperfusion complex was seen in 27 out of 498 patients (5.5%). Again, CT findings in a pediatric group with blunt abdominal trauma were evaluated by Taylor et al (1), and they reported the incidence as 0.01%. In our study, this incidence is 0.16%.…”
Section: Discussionmentioning
confidence: 99%